Analisi Pengakuan dan Pengukuran Wakaf Tidak Bergerak dalam Meningkatkan Transparansi untuk Kemaslahatan Umat di BWI Siak - Winda Chrisdafia; Khodijah Ishak; Zakaria Batubara (Comit: Communication, Information and Technology Journal, 2025)
This research was conducted to analyze the recognition and measurement of immovable waqf (WTB) in improving transparency for the benefit of the people at the Indonesian Waqf Board Siak Regency. The study employed qualitative methods, with data collected through interviews and questionnaires, using the Analytical Network Process (ANP) for data analysis. The findings indicated that several Masalahs persisted in waqf management, such as non-compliance with financial reporting guidelines, inadequate human resources, and uncertified waqf land. The study suggested improvements in these areas to enhance the transparency and efficiency of waqf management. The implications included recommendations for policy adjustments and increased stakeholder engagement in waqf practices